Upaya Pemerintah India dalam Menangani Clean Water Crisis di Kota Chennai tahun 2019 - 2021 - Cindana, Kadek Popy; Suwecawangsa, Adi Putra; Putri, Penny Kurnia (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2024)
Chennai was previously a wet city with many water distribution channels, rivers, reservoirs, and adequate drainage, but in 2019 faced a water crisis exacerbated by urbanization and extreme climate change. The severe clean water crisis made the Indian government announce that Chennai is a metropolitan city that should have the potential to become a water-resistant city, facing a water crisis. The clean water crisis is exacerbated by low rainfall, which has caused reservoir levels to drop so that the city does not have enough water reserves for Chennai residents' daily need. The Indian government has also begun to make various efforts to deal with the water crisis that has occurred in the city of Chennai. This study discusses the Indian government's local efforts that directly involve the community, such as the ‘Water Conservation Campaign’, and international efforts in dealing with this Chennai water crisis through international cooperation with the Netherlands, Denmark, and the United States. Keywords : Chennai, Climate Change, Indian Government, International Cooperation, Water Crisis